2003
DOI: 10.1254/jphs.93.501
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Protects Against Carbon Tetrachloride Hepatotoxicity in Mice

Abstract: Abstract. In the present study, the hepatoprotective effect of metformin (Met), a dimethylbiguanide anti-hyperglycemic, was examined in a mouse model of liver damage induced by chronic repeated administration of carbon tetrachloride (CCl 4 ) (5 m l / kg, twice a week for 12 weeks). Met, when given orally in drinking water at an estimated daily dose of 25 or 50 mg / kg for 10 weeks starting 2 weeks after CCl 4 challenge, protected against CCl 4 hepatotoxicity. The results indicate that the hepatoprotection affo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 13 publications
4
19
0
Order By: Relevance
“…Metformin is known to protect liver against injury induced by various drugs such as carbon tetrachloride (14), methotrexate (15), and acetaminophen (16). It has been demonstrated that HMGB1 released from necrotic hepatocytes plays a critical role in the acetaminophen-induced liver injury model by accelerating the primary injury (26) as the liver injury is drastically reduced in hepatocyte-specific HMGB1 knock out mice (36) or by administration of anti-HMGB1-neutralizing antibody (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin is known to protect liver against injury induced by various drugs such as carbon tetrachloride (14), methotrexate (15), and acetaminophen (16). It has been demonstrated that HMGB1 released from necrotic hepatocytes plays a critical role in the acetaminophen-induced liver injury model by accelerating the primary injury (26) as the liver injury is drastically reduced in hepatocyte-specific HMGB1 knock out mice (36) or by administration of anti-HMGB1-neutralizing antibody (41).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, metformin has hepatoprotective effects; it improves non-alcoholic steatohepatitis in humans (12) and prevents alcohol- and drug-induced liver injury in mice (1316). Because inflammation is a major contributor to these diseases (17), metformin could protect these diseases at least through its anti-inflammatory function (46, 18, 19).…”
Section: Introductionmentioning
confidence: 99%
“…A 500 mg tablet was dissolved in DW, and the drug was given to the rabbits according to body weight once daily through a stomach tube. [1819]…”
Section: Methodsmentioning
confidence: 99%
“…Products of lipid peroxidation may cause damage to the biological membranes leading to serious cellular injury and leakage of serum marker enzymes like AST, ALT and ALP (Cotran et al, 1994) and finally cell death (Wei, 1998). The prevention of this phenomenon can be considered as hepatoprotective activity (Poon et al, 2003). Estimations of serum transaminases and ALP are the most sensitive tests for diagnosis of liver diseases (Mahendale et al, 1985).…”
Section: Hepatoprotective Activitymentioning
confidence: 99%